2001
DOI: 10.1046/j.1364-3703.2001.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potato genes induced during colonization by Phytophthora infestans

Abstract: Summary Suppression Subtractive Hybridization (SSH) was applied in a search for genes induced during the compatible interaction between Phytophthora infestans and potato. Using potato leaves that had been treated with benzo(1,2,3)thiadiazole-7-carbothioic acid S-methylester (BTH) as the control tissue, a low redundancy library with a relatively low frequency of the classic plant Pathogenesis-Related (PR) genes was generated. 288 of the clones were screened for induced sequences using Inverse Northern analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 50 publications
4
52
0
1
Order By: Relevance
“…Tissue from the mating zone was harvested after 6 days. PN, PO (unsubtracted potato interactions)-as described (Beyer et al 2001), zoospores were spot-inoculated onto leaves from cv. Bintje and, after 6 days, tissue was harvested from within and outside the lesion for libraries PN and PO, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue from the mating zone was harvested after 6 days. PN, PO (unsubtracted potato interactions)-as described (Beyer et al 2001), zoospores were spot-inoculated onto leaves from cv. Bintje and, after 6 days, tissue was harvested from within and outside the lesion for libraries PN and PO, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Bintje and, after 6 days, tissue was harvested from within and outside the lesion for libraries PN and PO, respectively. PU, PW, PX (in vitro potato interactions)-as described (Beyer et al 2001), mycelia were grown in rye broth for 6 days, washed with water, and placed in water or on a potato leaf floating in water to generate control and tester samples, respectively. Both control and tester samples were pooled from 4-, 8-, and 24-h time-points.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches exist for isolating such differentially expressed genes (reviewed by Birch et al, 2003). A PCR-based method called suppression subtractive hybridization (SSH) has been used to isolate potato genes upregulated following P. infestans challenge Avrova et al, 1999Avrova et al, , 2004Beyer et al, 2001), and to identify P. infestans genes that are upregulated in the interaction with potato (Beyer et al, 2002). However, despite the ability to enrich for pathogen transcripts, SSH cDNA libraries constructed from host-oomycete interactions still yield a majority proportion of host sequences (Bittner-Eddy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that WRKYTFs have regulatory roles in signaling and modulation pathways of various molecular and physiological processes like seed germination, pollen development, biomass accumulation, and flowering regulation, and are also involved in the biosynthesis of secondary metabolites (Sun et al, 2003;Rushton et al, 2012;Yu et al, 2013). The WRKY TFs have also shown defense responses to different abiotic stresses, including heat, cold, water deficiency, and salinity (Wu et al, 2009;Jiang and Deyholos, 2009;Niu et al, 2012) and different biotic stresses, such as fungal, and viral, and bacterial infection (Beyer et al, 2001;Huh et al, 2012;Pan and Jiang, 2014).…”
Section: Introductionmentioning
confidence: 99%